Sprawozdanie z międzynarodowej konferencji naukowej. Ryga 4-5 października 2018 r. - Kulska, Joanna (Chrześcijaństwo-Świat-Polityka, 2019)
Sprawozdanie z międzynarodowej konferencji naukowej. Ryga 4-5 października 2018 r.